Pengaruh Work-Life Balance dan Beban Kerja Terhadap Stres Kerja PNS SMAN 1 Luwu Timur - Saing, Nurhalizah; Burhanuddin, Burhanuddin; Hamka, Rezky Amalia (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study aims to analyze the effect of work-life balance and workload on the work stress of civil servants (PNS) at SMAN 1 Luwu Timur. The study used a quantitative approach with a survey method. Data were collected through questionnaires distributed to 42 civil servants at SMAN 1 Luwu Timur. Data analysis was performed using multiple linear regression to test the effect of work-life balance and workload variables on work stress. The results showed that work-life balance did not significantly affect the work stress of civil servants at SMAN 1 Luwu Timur, while workload significantly affected work stress. Simultaneously, work-life balance and workload significantly affected work stress. These findings indicate that workload is the main factor affecting the level of work stress among civil servants.